Filantropi Sosial Budaya: Tradisi Lokal, Solidaritas Mekanik-Organisasi, dan Dinamika - Iqbal Arpannudin; Yayuk Hidayah; Nabila Ihza Nur Muttaqi; Nita Maghfiratul Jannah (Research and Development Agency Ministry of Home Affairs, 2025)
Philanthropy in Indonesia is deeply rooted in local traditions and the spirit of communal cooperation, making it a fundamental aspect of social life. The concept of citizenship in Indonesia goes beyond legal and political definitions, encompassing socio-cultural values expressed through diverse philanthropic practices. This study explores how local traditions and the dynamics between mechanical and organic solidarity shape the socio-cultural framework of philanthropy and influence civic development. The researchers surveyed 387 respondents across seven key regions: Yogyakarta, Bandung, Jakarta, Makassar, Medan, Denpasar, and Samarinda. Data collection focused on communal awareness, traditional practices, and the roles of solidarity in charitable efforts. Multiple regression analysis revealed that local traditions contribute 35% to strengthening philanthropic values. Mechanical solidarity, rooted in shared beliefs, accounts for 25%, while organic solidarity, driven by functional roles, contributes 20%. The interaction between tradition and modernity adds another 20%. These findings highlight that cultural traditions and the combination of mechanical and organic solidarity are vital foundations for building societal awareness. The research underscores the importance of stronger collaboration between government bodies and communities to incorporate these cultural elements into Indonesia's modern, citizenship-oriented philanthropic movements.